PEDAGOGICAL ASPECTS OF PREPARING HIGH SCHOOL STUDENTS FOR MILITARY SERVICE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The future Defender of the Fatherland should form the necessary moral, spiritual and combat qualities, and where necessary, he should mention the elements of military knowledge. The future Defender of the Fatherland should form the necessary moral, spiritual and combat qualities, and where necessary, he should mention the elements of military knowledge. It will be discussed about pedagogical aspects of preparing high school students for military service.